2014
DOI: 10.1016/j.ijhydene.2014.03.214
|View full text |Cite
|
Sign up to set email alerts
|

High glass forming ability correlated with microstructure and hydrogen storage properties of a Mg–Cu–Ag–Y glass

Abstract: Thermal characterization of an as-cast Mg 54 Cu 28 Ag 7 Y 11 bulk metallic glass revealed that this alloy exhibits excellent glass forming ability. High-resolution X-ray diffraction study and transmission electron microscopy show that heating and isothermal annealing treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 42 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…The corresponding linear heating DSC thermogram exhibits typical features of a metallic glass, including the glass transition (T g = 439K), followed by a three-stage crystallization sequence characterized by T x1 = 471 K, T x2 = 579 K and T x3 = 648 K exothermic transformations (see Figure 2). The width of the supercooled liquid region obtained as ∆T x = T x1,onset − T g corresponds to a remarkably high GFA (∆T x = 32 K), in accordance with other Mg-based glasses [24]. The high value of ∆T x suggests that the undercooled liquid may have a strong resistance to crystallization either by thermal activation or by SPD.…”
Section: Characterization Of the As-spun Ribbonsupporting
confidence: 85%
See 2 more Smart Citations
“…The corresponding linear heating DSC thermogram exhibits typical features of a metallic glass, including the glass transition (T g = 439K), followed by a three-stage crystallization sequence characterized by T x1 = 471 K, T x2 = 579 K and T x3 = 648 K exothermic transformations (see Figure 2). The width of the supercooled liquid region obtained as ∆T x = T x1,onset − T g corresponds to a remarkably high GFA (∆T x = 32 K), in accordance with other Mg-based glasses [24]. The high value of ∆T x suggests that the undercooled liquid may have a strong resistance to crystallization either by thermal activation or by SPD.…”
Section: Characterization Of the As-spun Ribbonsupporting
confidence: 85%
“…The high value of ∆T x suggests that the undercooled liquid may have a strong resistance to crystallization either by thermal activation or by SPD. The apparent activation energy values of the T x1 , T x2 and T x3 crystallization transformations were determined from the slope of the Kissinger plot (see the inset of Figure 2), and the obtained values (E a,Tx1 = 210 kJ/mol, E a,Tx1 = 188 kJ/mol and E a,Tx1 = 312 kJ/mol) also indicate high thermal stability, with these values being slightly higher than those obtained for Mg 54 Cu 28 Ag 7 Y 11 [24]. The total enthalpy release (∆H) corresponding to the multi-step crystallization process is ∆H = 105 J/g.…”
Section: Characterization Of the As-spun Ribbonmentioning
confidence: 98%
See 1 more Smart Citation
“…A complex transformation behaviour during hydrogen absorption/desorption was explored by in-situ X-ray synchrotron radiation of the Mg-Ni-La system, including a previously non-reported early stage formation of a La 2 Mg 17 H ~1.0 solid solution [113]. Detailed thermal characterization of a Mg 54 Cu 28 Ag 7 Y 11 BMG revealed that this composition has an excellent glass forming ability [114]. High pressure hydrogen-sorption experiments pointed out that the as-cast fully amorphous alloy exhibits the largest enthalpy of desorption, compared to the partially and fully crystallized states having similar concentrations.…”
Section: Hydrogen Storage In the Non-equilibrium Mg-(ni-cu)-(y-ce) Sy...mentioning
confidence: 99%
“…High pressure hydrogen-sorption experiments pointed out that the as-cast fully amorphous alloy exhibits the largest enthalpy of desorption, compared to the partially and fully crystallized states having similar concentrations. Since the fully crystallized sample does not desorb hydrogen at all, it can be assumed that the disordered local atomic structure of the glass is accountant for the hydrogen release [114].…”
Section: Hydrogen Storage In the Non-equilibrium Mg-(ni-cu)-(y-ce) Sy...mentioning
confidence: 99%